COMPARISON OF BEHAVIORAL PROFILES FOR ANXIETY‐RELATED COMORBIDITIES INCLUDING ADHD AND SELECTIVE MUTISM IN CHILDREN. Issue 9 (22nd March 2013) - Levin‐Decanini, Tal; Connolly, Sucheta D.; Simpson, David; Suarez, Liza; Jacob, Suma
<x xml:space="preserve">Abstract</x> Background Elucidating differences in social‐behavioral profiles of children with comorbid presentations, utilizing caregiver as well as teacher reports, will refine our understanding of how contextual symptoms vary across anxiety‐related disorders. Methods In our pediatric anxiety clinic, the most frequent diagnoses and comorbidities were mixed anxiety (MA; ≥ 1 anxiety disorder; N = 155), anxiety with comorbid attention‐deficit hyperactivity disorder (MA/ADHD, N = 47) and selective mutism (SM, N = 48). Behavioral measures (CPRS, CTRS) were analyzed using multiple one‐way multivariate analyses of covariance tests. Differences between the three diagnostic groups were examined using completed parent and teacher reports (N = 135, 46, and 48 for MA, MA/ADHD, and SM groups, respectively). Results Comparisons across the MA, MA/ADHD, and SM groups indicate a significant multivariate main effect of group for caregiver and teacher responses (P < 0.01). Caregivers reported that children with SM are similar in profile to those with MA, and both groups were significantly different from the MA/ADHD group. Teachers reported that children with SM had more problems with social behaviors than with the MA or MA/ADHD groups. Further comparison indicates a significant main effect of group (P < 0.001), such that children with SM have the greatest differences in behavior observed by teachers versus caregivers. Conclusions Clinical profiles between MA/ADHD, MA, and SM groups varied, illustrating the importance of multi‐rater assessment scales to capture subtle distinctions and to inform treatment planning given that comorbidities occur frequently in children who present with anxiety.